Genetic loci associated with plasma phospholipid n-3 fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Lemaitre, Rozenn N; Tanaka, Toshiko; Tang, Weihong; Manichaikul, Ani; Foy, Millennia; Kabagambe, Edmond K; Nettleton, Jennifer A; King, Irena B; Weng, Lu-Chen; Bhattacharya, Sayanti; Bandinelli, Stefania; Bis, Joshua C; et al. (PLoS Genet, 2011)
Long-chain n-3 polyunsaturated fatty acids (PUFAs) can derive from diet or from α-linolenic acid (ALA) by elongation and desaturation. We investigated the association of common genetic variation with plasma phospholipid levels of the four major n-3 PUFAs by performing genome-wide association studies in five population-based cohorts comprising 8,866 subjects of European ancestry. Minor alleles of SNPs in FADS1 and FADS2 (desaturases) were associated with higher levels of ALA (p = 3 x 10⁻⁶⁴) and lower levels of eicosapentaenoic acid (EPA, p = 5 x 10⁻⁵⁸) and docosapentaenoic acid (DPA, p = 4 x 10⁻¹⁵⁴). Minor alleles of SNPs in ELOVL2 (elongase) were associated with higher EPA (p = 2 x 10⁻¹²) and DPA (p = 1 x 10⁻⁴³) and lower docosahexaenoic acid (DHA, p = 1 x 10⁻¹⁵). In addition to genes in the n-3 pathway, we identified a novel association of DPA with several SNPs in GCKR (glucokinase regulator, p = 1 x 10⁻⁸). We observed a weaker association between ALA and EPA among carriers of the minor allele of a representative SNP in FADS2 (rs1535), suggesting a lower rate of ALA-to-EPA conversion in these subjects. In samples of African, Chinese, and Hispanic ancestry, associations of n-3 PUFAs were similar with a representative SNP in FADS1 but less consistent with a representative SNP in ELOVL2. Our findings show that common variation in n-3 metabolic pathway genes and in GCKR influences plasma phospholipid levels of n-3 PUFAs in populations of European ancestry and, for FADS1, in other ancestries.
Keywords: Alleles; Continental Population Groups; Fatty Acids, Omega-3; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide

Genome-wide association study identifies novel loci associated with concentrations of four plasma phospholipid fatty acids in the de novo lipogenesis pathway: results from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortiu - Wu, Jason H Y; Lemaitre, Rozenn N; Manichaikul, Ani; Guan, Weihua; Tanaka, Toshiko; Foy, Millennia; Kabagambe, Edmond K; Djoussé, Luc; Siscovick, David; Fretts, Amanda M; Johnson, Catherine; King, Irena B; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND- Palmitic acid (16:0), stearic acid (18:0), palmitoleic acid (16:1n-7), and oleic acid (18:1n-9) are major saturated and monounsaturated fatty acids that affect cellular signaling and metabolic pathways. They are synthesized via de novo lipogenesis and are the main saturated and monounsaturated fatty acids in the diet. Levels of these fatty acids have been linked to diseases including type 2 diabetes mellitus and coronary heart disease. METHODS AND RESULTS- Genome-wide association studies were conducted in 5 population-based cohorts comprising 8961 participants of European ancestry to investigate the association of common genetic variation with plasma levels of these 4 fatty acids. We identified polymorphisms in 7 novel loci associated with circulating levels of ≥1 of these fatty acids. ALG14 (asparagine-linked glycosylation 14 homolog) polymorphisms were associated with higher 16:0 (P=2.7×10(-11)) and lower 18:0 (P=2.2×10(-18)). FADS1 and FADS2 (desaturases) polymorphisms were associated with higher 16:1n-7 (P=6.6×10(-13)) and 18:1n-9 (P=2.2×10(-32)) and lower 18:0 (P=1.3×10(-20)). LPGAT1 (lysophosphatidylglycerol acyltransferase) polymorphisms were associated with lower 18:0 (P=2.8×10(-9)). GCKR (glucokinase regulator; P=9.8×10(-10)) and HIF1AN (factor inhibiting hypoxia-inducible factor-1; P=5.7×10(-9)) polymorphisms were associated with higher 16:1n-7, whereas PKD2L1 (polycystic kidney disease 2-like 1; P=5.7×10(-15)) and a locus on chromosome 2 (not near known genes) were associated with lower 16:1n-7 (P=4.1×10(-8)). CONCLUSIONS- Our findings provide novel evidence that common variations in genes with diverse functions, including protein-glycosylation, polyunsaturated fatty acid metabolism, phospholipid modeling, and glucose- and oxygen-sensing pathways, are associated with circulating levels of 4 fatty acids in the de novo lipogenesis pathway. These results expand our knowledge of genetic factors relevant to de novo lipogenesis and fatty acid biology.
Keywords: Adult; Aged; Chromosomes, Human, Pair 2; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Fatty Acids, Monounsaturated; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Lipogenesis; Male; Middle Aged; Oleic Acid; Palmitic Acid; Polymorphism, Single Nucleotide; Stearic Acids

Genome-wide association study of plasma N6 polyunsaturated fatty acids within the cohorts for heart and aging research in genomic epidemiology consortium. - Guan, Weihua; Steffen, Brian T; Lemaitre, Rozenn N; Wu, Jason H Y; Tanaka, Toshiko; Manichaikul, Ani; Foy, Millennia; Rich, Stephen S; Wang, Lu; Nettleton, Jennifer A; Tang, Weihong; Gu, Xiangjun; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Omega6 (n6) polyunsaturated fatty acids (PUFAs) and their metabolites are involved in cell signaling, inflammation, clot formation, and other crucial biological processes. Genetic components, such as variants of fatty acid desaturase (FADS) genes, determine the composition of n6 PUFAs. METHODS AND RESULTS: To elucidate undiscovered biological pathways that may influence n6 PUFA composition, we conducted genome-wide association studies and meta-analyses of associations of common genetic variants with 6 plasma n6 PUFAs in 8631 white adults (55% women) across 5 prospective studies. Plasma phospholipid or total plasma fatty acids were analyzed by similar gas chromatography techniques. The n6 fatty acids linoleic acid (LA), γ-linolenic acid (GLA), dihomo-GLA, arachidonic acid, and adrenic acid were expressed as percentage of total fatty acids. We performed linear regression with robust SEs to test for single-nucleotide polymorphism-fatty acid associations, with pooling using inverse-variance-weighted meta-analysis. Novel regions were identified on chromosome 10 associated with LA (rs10740118; P=8.1×10(-9); near NRBF2), on chromosome 16 with LA, GLA, dihomo-GLA, and arachidonic acid (rs16966952; P=1.2×10(-15), 5.0×10(-11), 7.6×10(-65), and 2.4×10(-10), respectively; NTAN1), and on chromosome 6 with adrenic acid after adjustment for arachidonic acid (rs3134950; P=2.1×10(-10); AGPAT1). We confirmed previous findings of the FADS cluster on chromosome 11 with LA and arachidonic acid, and further observed novel genome-wide significant association of this cluster with GLA, dihomo-GLA, and adrenic acid (P=2.3×10(-72), 2.6×10(-151), and 6.3×10(-140), respectively). CONCLUSIONS: Our findings suggest that along with the FADS gene cluster, additional genes may influence n6 PUFA composition.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 6; Fatty Acid Desaturases; Fatty Acids, Omega-6; Female; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

Large-scale genome-wide association studies and meta-analyses of longitudinal change in adult lung function. - Tang, Wenbo; Kowgier, Matthew; Loth, Daan W; Soler Artigas, Maria; Joubert, Bonnie R; Hodge, Emily; Gharib, Sina A; Smith, Albert V; Ruczinski, Ingo; Gudnason, Vilmundur; Mathias, Rasika A; Harris, Tamara B; et al. (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified numerous loci influencing cross-sectional lung function, but less is known about genes influencing longitudinal change in lung function. METHODS: We performed GWAS of the rate of change in forced expiratory volume in the first second (FEV1) in 14 longitudinal, population-based cohort studies comprising 27,249 adults of European ancestry using linear mixed effects model and combined cohort-specific results using fixed effect meta-analysis to identify novel genetic loci associated with longitudinal change in lung function. Gene expression analyses were subsequently performed for identified genetic loci. As a secondary aim, we estimated the mean rate of decline in FEV1 by smoking pattern, irrespective of genotypes, across these 14 studies using meta-analysis. RESULTS: The overall meta-analysis produced suggestive evidence for association at the novel IL16/STARD5/TMC3 locus on chromosome 15 (P  =  5.71 × 10(-7)). In addition, meta-analysis using the five cohorts with ≥3 FEV1 measurements per participant identified the novel ME3 locus on chromosome 11 (P  =  2.18 × 10(-8)) at genome-wide significance. Neither locus was associated with FEV1 decline in two additional cohort studies. We confirmed gene expression of IL16, STARD5, and ME3 in multiple lung tissues. Publicly available microarray data confirmed differential expression of all three genes in lung samples from COPD patients compared with controls. Irrespective of genotypes, the combined estimate for FEV1 decline was 26.9, 29.2 and 35.7 mL/year in never, former, and persistent smokers, respectively. CONCLUSIONS: In this large-scale GWAS, we identified two novel genetic loci in association with the rate of change in FEV1 that harbor candidate genes with biologically plausible functional links to lung function.
Keywords: Adult; Chromosomes, Human, Pair 11; Female; Gene Expression Regulation; Genetic Loci; Genome-Wide Association Study; Humans; Longitudinal Studies; Male; Respiration

Dietary fatty acids modulate associations between genetic variants and circulating fatty acids in plasma and erythrocyte membranes: Meta-analysis of nine studies in the CHARGE consortium. - Smith, Caren E; Follis, Jack L; Nettleton, Jennifer A; Foy, Millennia; Wu, Jason H Y; Ma, Yiyi; Tanaka, Toshiko; Manichakul, Ani W; Wu, Hongyu; Chu, Audrey Y; Steffen, Lyn M; Fornage, Myriam; et al. (Mol Nutr Food Res, 2015)
SCOPE: Tissue concentrations of omega-3 fatty acids may reduce cardiovascular disease risk, and genetic variants are associated with circulating fatty acids concentrations. Whether dietary fatty acids interact with genetic variants to modify circulating omega-3 fatty acids is unclear. We evaluated interactions between genetic variants and fatty acid intakes for circulating alpha-linoleic acid, eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid. METHODS AND RESULTS: We conducted meta-analyses (N = 11 668) evaluating interactions between dietary fatty acids and genetic variants (rs174538 and rs174548 in FADS1 (fatty acid desaturase 1), rs7435 in AGPAT3 (1-acyl-sn-glycerol-3-phosphate), rs4985167 in PDXDC1 (pyridoxal-dependent decarboxylase domain-containing 1), rs780094 in GCKR (glucokinase regulatory protein), and rs3734398 in ELOVL2 (fatty acid elongase 2)). Stratification by measurement compartment (plasma versus erthyrocyte) revealed compartment-specific interactions between FADS1 rs174538 and rs174548 and dietary alpha-linolenic acid and linoleic acid for docosahexaenoic acid and docosapentaenoic acid. CONCLUSION: Our findings reinforce earlier reports that genetically based differences in circulating fatty acids may be partially due to differences in the conversion of fatty acid precursors. Further, fatty acids measurement compartment may modify gene-diet relationships, and considering compartment may improve the detection of gene-fatty acids interactions for circulating fatty acid outcomes.
Keywords: Acetyltransferases; Acyltransferases; Adaptor Proteins, Signal Transducing; Carboxy-Lyases; Diet; Docosahexaenoic Acids; Eicosapentaenoic Acid; Erythrocyte Membrane; Fatty Acid Desaturases; Fatty Acids; Fatty Acids, Omega-3; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Genetic loci associated with circulating levels of very long-chain saturated fatty acids. - Lemaitre, Rozenn N; King, Irena B; Kabagambe, Edmond K; Wu, Jason H Y; McKnight, Barbara; Manichaikul, Ani; Guan, Weihua; Sun, Qi; Chasman, Daniel I; Foy, Millennia; Wang, Lu; Zhu, Jingwen; et al. (J Lipid Res, 2015)
Very long-chain saturated fatty acids (VLSFAs) are saturated fatty acids with 20 or more carbons. In contrast to the more abundant saturated fatty acids, such as palmitic acid, there is growing evidence that circulating VLSFAs may have beneficial biological properties. Whether genetic factors influence circulating levels of VLSFAs is not known. We investigated the association of common genetic variation with plasma phospholipid/erythrocyte levels of three VLSFAs by performing genome-wide association studies in seven population-based cohorts comprising 10,129 subjects of European ancestry. We observed associations of circulating VLSFA concentrations with common variants in two genes, serine palmitoyl-transferase long-chain base subunit 3 (SPTLC3), a gene involved in the rate-limiting step of de novo sphingolipid synthesis, and ceramide synthase 4 (CERS4). The SPTLC3 variant at rs680379 was associated with higher arachidic acid (20:0 , P = 5.81 × 10(-13)). The CERS4 variant at rs2100944 was associated with higher levels of 20:0 (P = 2.65 × 10(-40)) and in analyses that adjusted for 20:0, with lower levels of behenic acid (P = 4.22 × 10(-26)) and lignoceric acid (P = 3.20 × 10(-21)). These novel associations suggest an inter-relationship of circulating VLSFAs and sphingolipid synthesis.
Keywords: Cohort Studies; Fatty Acids; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans

Genetic loci associated with circulating phospholipid trans fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Mozaffarian, Dariush; Kabagambe, Edmond K; Johnson, Catherine O; Lemaitre, Rozenn N; Manichaikul, Ani; Sun, Qi; Foy, Millennia; Wang, Lu; Wiener, Howard; Irvin, Marguerite R; Rich, Stephen S; Wu, Hongyu; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Circulating trans fatty acids (TFAs), which cannot be synthesized by humans, are linked to adverse health outcomes. Although TFAs are obtained from diet, little is known about subsequent influences (e.g., relating to incorporation, metabolism, or intercompetition with other fatty acids) that could alter circulating concentrations and possibly modulate or mediate impacts on health. OBJECTIVE: The objective was to elucidate novel biologic pathways that may influence circulating TFAs by evaluating associations between common genetic variation and TFA biomarkers. DESIGN: We performed meta-analyses using 7 cohorts of European-ancestry participants (n = 8013) having measured genome-wide variation in single-nucleotide polymorphisms (SNPs) and circulating TFA biomarkers (erythrocyte or plasma phospholipids), including trans-16:1n-7, total trans-18:1, trans/cis-18:2, cis/trans-18:2, and trans/trans-18:2. We further evaluated SNPs with genome-wide significant associations among African Americans (n = 1082), Chinese Americans (n = 669), and Hispanic Americans (n = 657) from 2 of these cohorts. RESULTS: Among European-ancestry participants, 31 SNPs in or near the fatty acid desaturase (FADS) 1 and 2 cluster were associated with cis/trans-18:2; a top hit was rs174548 (β = 0.0035, P = 4.90 × 10(-15)), an SNP previously associated with circulating n-3 and n-6 polyunsaturated fatty acid concentrations. No significant association was identified for other TFAs. rs174548 in FADS1/2 was also associated with cis/trans-18:2 in Hispanic Americans (β = 0.0053, P = 1.05 × 10(-6)) and Chinese Americans (β = 0.0028, P = 0.002) but not African Americans (β = 0.0009, P = 0.34); however, in African Americans, fine mapping identified a top hit in FADS2 associated with cis/trans-18:2 (rs174579: β = 0.0118, P = 4.05 × 10(-5)). The association between rs174548 and cis/trans-18:2 remained significant after further adjustment for individual circulating n-3 and n-6 fatty acids, except arachidonic acid. After adjustment for arachidonic acid concentrations, the association between rs174548 and cis/trans-18:2 was nearly eliminated in European-ancestry participants (β-coefficient reduced by 86%), with similar reductions in Hispanic Americans and Chinese Americans. CONCLUSIONS: Our findings provide novel evidence for genetic regulation of cis/trans-18:2 by the FADS1/2 cluster and suggest that this regulation may be influenced/mediated by concentrations of arachidonic acid, an n-6 polyunsaturated fat.
Keywords: African Americans; Arachidonic Acid; Asian Americans; Biomarkers; European Continental Ancestry Group; Fatty Acids, Omega-6; Gene Frequency; Genetic Association Studies; Genetic Loci; Genotyping Techniques; Humans; Phospholipids; Polymorphism, Single Nucleotide; Trans Fatty Acids